Proximal tibial resections and reconstructions: Clinical outcome of 225 patients1. Issue 4 (17th July 2012) - Mavrogenis, Andreas F.; Pala, Elisa; Angelini, Andrea; Ferraro, Andrea; Ruggieri, Pietro
Abstract Background Previous studies reported variable outcome of proximal tibial resections and reconstructions. Therefore, we evaluated the survival, Musculoskeletal Tumor Society (MSTS) function, and complications of patients and reconstructions in this location. Materials and Methods We reviewed the files of 225 patients with proximal tibial tumors treated with proximal tibial resection, fixed or rotating hinge megaprosthetic reconstruction and extensor mechanism reattachment using sutures, mechanical clamping, artificial ligaments, and/or gastrocnemius flap from 1985 to 2010 (mean follow‐up, 90 months; median, 56; range, 2–294). Survival of patients and reconstructions, type of hinge, extensor mechanism reconstruction, MSTS function, and complications were analyzed. Results Survival of patients with sarcomas was 68% and 62% at 5 and 10 years. Survival of megaprosthetic reconstructions was 82% and 78% at 5 and 10 years, without any difference between fixed and rotating hinge megaprostheses. MSTS function was significantly better in univariate and multivariate analysis for rotating compared to fixed hinge megaprostheses, without any difference between the types of extensor mechanism reconstructions. Most common complications were infection (12%), aseptic loosening (6%), and extensor mechanism rupture (3%). Conclusions Rotating hinge proximal tibia megaprosthetic reconstructions have better function compared to fixed hinge, regardless of the type of extensor mechanism reconstruction. J. Surg. Oncol. 2013;107:335–342. © 2012 Wiley Periodicals, Inc.